The Effect of Accounting Information Systems and E-Commerce on Decision Making in Entrepreneurship (Case Study of MSMEs in Palembang City) - Yolinda Rosiasti; RM. Rum Hendarmin; Andini Utari Putri (International Journal of Community Service & Engagement, 2023)
The objective of this study are to analyze the effect of accounting information systems and e-commerce on decision-making in entrepreneurship in micro, small and medium enterprises in Palembang city. Data was obtained from observation, literature study, and questionnaires. The sample in this study was 71 respondents. Data were analyzed using multiple linear regression. Before being analyzed, the data were tested by normality test, multicollinearity test, and heteroscedasticity test. The results of this study prove that accounting information systems have a significant effect on decision-making in entrepreneurship, while e-commerce has no effect on decision-making in entrepreneurship. The results of this study are expected to be taken into consideration in making decisions in entrepreneurship to improve accounting information systems and e-commerce.